PELAKSANAAN PAGANG GADAI TANAH PUSAKO TINGGI PADA MASYARAKAT MINANGKABAU (STUDI DI KECAMATAN NAN SABARIS KABUPATEN PADANG PARIAMAN PROVINSI SUMATERA BARAT) - INDAH FIRMAJA SARI (PREMISE LAW JURNAL, 2017)
DOSEN PEMBIMBING:1. Edy Ikhsan2. Yefrizawaty3. Utary Maharany Barus Mortgaging tanah pusako tinggi (ancestral land) in Minangkabau is also called „pagang gadai‟ which is done when it is in emergency such as „Mayik tabujua ateh rumah‟ (the deceased lies in the house), Gadih gadang alun balaki (A girl who can be a spinster), Rumah gadang katirisan (rumah gadang is utterly damaged), and „Membangkik batang terandam‟ (to save from oblivion). Pagang gadai in Nan Sabaris Subdistrict is social matters to help each other in the adat community of Minangkabau. The mortgage will be redeemed without any time period.Keywords: Pagang Gadai, Tanah Pusako Tinggi, Nan Sabaris Subdistrict